Studi analisis simulasi kekuatan beban pada alat bantu pembuatan lubang dengan sudut kemiringan 45 derajat - Dr. Fatahul Arifin, S.T., Dipl.Eng.EPD., M.Eng.Sc; Dwi Arnoldi, S.T., M.T.; Ella Sundari, S.T., M.T.; Fenoria Putri, S.T., M.T.; Feby Agasa; Yudha Ramadhan; Gustaf Susetyo; Dr. Yusuf Dewantoro Herlambang, S.T., M.T. (Politeknik Negeri Lhokseumawe, 2020)
Jig and Fixture 45 degree bore is a tool which is used to make hole the degree 45 degrees. The goal of study is design and analyze the strength of the frame and assembly with variations in position of load and value from 100 kg to 500 kg. The results of the stress analysis feature with finite element Analysis (FEA) are von misses stress, displacement, and safety factor. The Frame uses a hollow carbon steel of 20 mm x 20 mm, a material of carbon steel. The frame length is 300 mm, the width is 300 mm, the height is 270 mm, dimension of the tool is 300 mm x 300mm x 270 mm. The simulation results are; the safety factor of frame maximum is 7.08 with a load of 100 kg, while minimum is 1.42 with load 500 kg. Whereas, the overall assembly safety factor maximum is 3.88 with loads 100 kg and minimum is 0.82 with load 500 kg. The unsafe location is on the upper of connection frame, while for the overall assembly is on the buffer of shaft component.